Detection of Attacks on Apache2 Web Server Using Genetic Algorithm Based On Jaro Winkler Algorithm - M Rizqi Maulana (Universitas Medan Area, 2020)
Web server is software that provides data services in the form of HTTP (Hypertext Transfer Protocol) requests and responses in the form of HTML documents (Hypertext Markup Language) with the aim of managing data in the form of text files, images, videos and files. But in managing large amounts of data, good security monitoring is needed so that the data stored on the web server is not easily hacked. To protect the web server from hackers need an application to detect activities that are considered suspicious or possible hacking activities. By utilizing logs from a web server that is processed using the Jaro Winkler algorithm to see hacking attempts that produce a matrix and hacking activity reports to the admin. Thus the web server admin can see suspicious activity on the web server directly.Keywords: Web Server, Jaro Winkler Algorithm.